Implementasi Sistem Informasi Geografis Berbasis Web dalam Penyusunan Profil Kependudukan - Sadewa Purba Sejati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has an impact on the economic and social sectors in RT 08 Kertodadi, Pakembinangun Village, Pakem District, Sleman Regency, Yogyakarta Special Region Province. The provision of population data as a complete document for applying for social assistance has been carried out by the government at the neighborhood level, but the available data is still conventional. The availability of conventional population data is caused by the lack of briefing on the use of information technology as a digital population data inventory tool. Efforts are being made to overcome the problem by providing training and assistance in the preparation of a digital population profile. The basic science used in this activity is a geographic information system (GIS) which is used as the basis of knowledge in a digital population data inventory. The end result of this activity is a digital-based population profile with spatial and regional values ​​that can be used to make an inventory of population dynamics quickly, easily, and transparently.